Tools and Algorithms for the Construction and Analysis of Systems 25 Years of TACAS: TOOLympics, Held as Part of ETAPS 2019, Prague, Czech Republic, April 6-11, 2019, Proceedings, Part III - Beyer, Dirk; Huisman, Marieke; Kordon, Fabrice; Steffen, Bernhard (Theoretical Computer Science and General Issues,, 2019)
This book is Open Access under a CC BY licence. .